how (x-2)(x+1) = (x-1)(x+3) solved ?
Asked by Angel Sanaf farooqui | 25th Sep, 2013, 08:35: PM
(x-2)(x+1) = (x-1)(x+3)
x2 - 2x + x - 2 = x2 - x + 3x - 3
-x - 2 = 2x - 3
This is clearly a linear equation (highest power of the variable x is 1).
Thus, the given equation is not a quadratic equation.
Answered by | 25th Sep, 2013, 09:58: PM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number